2017
DOI: 10.1038/s41598-017-00934-x
|View full text |Cite
|
Sign up to set email alerts
|

The adjuvant value of Andrographis paniculata in metastatic esophageal cancer treatment – from preclinical perspectives

Abstract: Esophageal cancer (EC) is the fourth and sixth leading cause of cancer-related deaths in China and United States, respectively. The dismal prognosis of EC is mainly attributed to distant metastases, which may not be overcome by chemotherapy alone. Hence, the use of alternative adjuvant treatments, such as herbal medicines, for metastatic EC remains a great desire of patients. Our previous study demonstrated the in vivo anti-tumor and in vitro anti-invasion activities of Andrographis paniculata (AP) in esophage… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
33
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

5
0

Authors

Journals

citations
Cited by 27 publications
(36 citation statements)
references
References 34 publications
(41 reference statements)
2
33
0
1
Order By: Relevance
“…The proportion of EC patients with EGFR overexpression ranges from 36.6% to 97%, and such overexpression is associated with lymph node metastasis, survival rate, and pathologic tumor stages (Zhang et al, ). The present data showed the reduced EGFR gene expression in APW‐treated cells as well as the decreased level of HER2 gene and protein after APW exposure as demonstrated in our previous study (Li et al, ), suggesting that ErbB signaling pathway is also contributed to the inhibitory effects of APW. Besides, the overexpression of PDGFRB enhanced the EC cell proliferation and migration ability through multiple signaling pathways (Song et al, ), and APW could down‐regulate such expressions.…”
Section: Discussionsupporting
confidence: 88%
See 4 more Smart Citations
“…The proportion of EC patients with EGFR overexpression ranges from 36.6% to 97%, and such overexpression is associated with lymph node metastasis, survival rate, and pathologic tumor stages (Zhang et al, ). The present data showed the reduced EGFR gene expression in APW‐treated cells as well as the decreased level of HER2 gene and protein after APW exposure as demonstrated in our previous study (Li et al, ), suggesting that ErbB signaling pathway is also contributed to the inhibitory effects of APW. Besides, the overexpression of PDGFRB enhanced the EC cell proliferation and migration ability through multiple signaling pathways (Song et al, ), and APW could down‐regulate such expressions.…”
Section: Discussionsupporting
confidence: 88%
“…The overexpression of ABC transporters are known for conferring multidrug resistance, which can elevate efflux of drugs from cancer cells, thereby diminish intracellular drug concentration (Hu et al, ; Sun, Patel, Kumar, & Chen, ). Our previous in vivo study showed that APW treatment enhanced the inhibitory effects of cisplatin plus 5‐FU on tumor growth (Li et al, ). APW also acted synergistic inhibitory effects with cisplatin and 5‐FU on motility of cancer cells in vitro (data not shown).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations